Ears, Environments, Ethics - Prendergast, Patrick (Department of Mechanical, Manufacturing and Biomedical Engineering, Trinity College Dublin, 2025)
Some aspects of mechanical engineering from the early 1980s to the mid 2020s are discussed. I begin by recalling my first meeting with Professor (then Dr) Henry Rice, and I describe some research we later did on the biomechanics of hearing. I also discuss work on E3, a strategic initiative to grow teaching and research activities in engineering and other STEM disciplines. E3 was in the planning for a long time. The final approval by the Trinity Board came in April 2018. Construction of the E3 Learning Foundry eventually commenced during Professor Rice’s time as Head of the School of Engineering (2016 – 2022). E3 stands for Engineering, Environment, and Emerging Technologies and I conclude by addressing a fourth E – Ethics. If engineering asks the question 'what can we do?’ ethics asks ‘what ought we do?’. Ethics provides a systematic way to think about the goal of E3 which has been described as ‘Balanced solutions for a better world’.
Perspectives on Engineering Mechanics and Dynamics. Essays in Honour of Henry Rice
PUBLISHED
Dublin